METHANOLIC BARK EXTRACT OF BRIDELIA FERRUGINEA: PHYTOCHEMICALS, ANTIOXIDANT POTENTIALS AND SPECTROSCOPIC CHARACTERIZATION - Omotunde, Oluwatoyin; Abiodun, Oluyide; Ojo, Ayomipo; Gurgur, Emmanuel (FUDMA Journal of Sciences, 2025)
Bridelia ferruginea is commonly utilized in African traditional medicine, yet extensive inquiries into its bioactive constituents remain limited. This study assesses the phytochemical composition, antioxidant properties, and spectroscopic characteristics of the methanolic bark extract of B. ferruginea. Standard phytochemical screening showed the presence of saponins, phenols, tannins, flavonoids, terpenoids, steroids, and phlobatannins, with phenols and terpenoids occurring in substantial quantities. Antioxidant properties were evaluated using recognized assays, comprising total phenolic and flavonoid content, ferric reducing antioxidant power (FRAP), Fe2+ chelation, and DPPH radical scavenging activity with ascorbic acid as control. The extract confirmed remarkable antioxidant capacity, with 50 % inhibition (IC) values for FRAP at 0.412 μg/mL, Fe2+ chelation activity of 7.12 μg/mL, and DPPH scavenging activity of 12.63 μg/mL, demonstrating significant potential in mitigating oxidative stress. FTIR analysis affirmed functional groups, including hydroxyl, carbonyl, ester, and aromatic systems related to bioactive compounds. UV-Vis spectra showed strong absorption around 230 nm, consistent with phenolic and flavonoid constituents. GC-MS analysis identified 24 compounds, comprising myricetin, quercetin, kaempferol, phytol, and zingiberene, several of which are associated with antioxidant, antimicrobial, and anti-inflammatory activities. These results offer scientific support for the plant’s traditional uses and point to its capacity as a natural source of antioxidants and medicinal agents.
Keywords: Bridelia Ferruginea; Phytochemicals; Antioxidant Potential; Traditional Medicine